KEMAMPUAN KOMUNIKASI INTERPERSONAL PEMIMPIN PERPUSTAKAAN UNIVERSITAS BENGKULU DENGAN PUSTAKAWAN - Daryono Daryono (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2020)
The objectives of this research are to describe and analyze  interpersonal communication ability of the leader with librarian in Library University of Bengkulu. This research employed descriptive by qualitative approach. Techniques of collected data by used observation, interview and documentation. Technique of data analysis by used qualitative inductive. The results of this research are showed interpersonal communication the leader Library University of Bengkulu. Firstly, openness aspect the leader of library quite open to every librarian, especially to reprimand the librarian who didn’t did their duties and responsibilities well. Secondly, emphaty aspect showed that the leader of library empathize to librarian who experience organizational injustice. Thirdly, support aspect showed that the leader of library provided full support for ideas and constructive input from librarian by conducting qustions-answers in connection with ideas and input submitted by librarian. Fourthly, positive aspect showed that the leader of library  clarify positive attitude that is conveyed directly to the librarian concerned and encourages the librarian positively to interact with each other. Fifthly, equality aspect showed that the leader of library  treat all of the librarian and library staff equal regardless  of gender, age, title, position, closeness, etc. Overall based on the five aspects it can be concluded that the interpersonal communication ability Library University of Bengkulu leader  with librarian are included in good category.